Total Plate Numbers and Coliforms in The Processing of Milkfish Without Spines (Chanos Chanos) in Household Indusrty in Banda Aceh - Nurliana, Nurliana; Aftari, Nailul; Sutriana, Amalia; Asmilia, Nuzul; Sari, Wahyu Eka (Jurnal Medika Veterinaria, 2023)
Microbial contamination of fish has the potential to cause product quality degradation and cause fishborne disease. Microbial contamination can occur at any stage of fish processing. This study aimed to determine the total plate count and coliform at each stage process of milkfish (Chanos chanos) boneless. Milkfishes were obtained from three processing stage, namely raw material (fresh fish) stage, the fish bone removal stage and the baking fish stage. The parameters observed were the number of colonies growing as total plate count and coliform as the most probable number (MPN). The results showed that the highest ALT contamination was found at the bone removal stage with an average of 1.7x104 CFU/g but this figure did not exceed the standard limit and the lowest was at the firing stage with an average of 1.2x103 CFU/g. The highest coliform was found in the fresh fish stage, namely 129 MPN/g and the lowest was 3 MPN/g. From this research, it can be concluded that the total microbial plate number does not exceed the SNI 7288: 2009 standard and the coliform exceed the SNI 7388: 2009 standard.